UJI KEMAMPUAN BEBERAPA KONSENTRASI EKSTRAK DAUN SELASIH UNGU (Ocimum sanctum L.) SEBAGAI ATRAKTAN HAMA LALAT BUAH PADA PERTANAMAN JAMBU BIJI (Psidium guajava L.) - Nadia Elly Oktaviani; Agus Sutikno; Desita Salbiah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Fruit flies is a major pest on guajava plants. The research was done in the Center of Agricultural Development and the Laboratory of Plant Pest, Faculty of Agriculture, University of Riau from January until March 2015. The way of controling this pest by usingatractant. The result showed that there were two species pest of fruit flies guajava,Bactrocera dorsalis Hendel and Bactrocera umbrosa Fabricius. The research showed thatBactrocera dorsalis Hendelthat also caughtwas 220, 780, 819, and 1409 fruit flies. The research showed that of 5, 8, 18 and 16 fruit flies. The concentration of 80% basil leaf extract could cacth a higher number of B. dorsalis, which is 282,20 fruit flie Key word: Fruit flies, Atractant, Ocimum sanctum L., Bactrocera dorsalis Hendel, Bactrocera umbrosa Fabricius and Psidium guajava L.